Patient-reported outcome measures in an outpatient parenteral antimicrobial therapy program: a prospective cohort study - Nadia Eberhard; Bruno Ledergerber; Andrea R Burch; Martin Ringer; Annelies S Zinkernagel; Marisa B Kaelin; Barbara Hasse (BMJ Open)
Objectives To evaluate the improvements in the mean Short Form-36 (SF-36) score (95% CI) from predischarge to postdischarge among prospective participants of a Swiss Outpatient Parenteral Antimicrobial Therapy (OPAT) programme using Patient Reported Outcomes.Design Prospective cohort study.Setting A public tertiary care hospital in Switzerland.Participants Patients enrolled in the University Hospital Zurich’s OPAT programme between October 2020 and September 2022. They were interviewed predischarge (interview 1) and 7–14 days postdischarge (interview 2) using a shortened, four-domain version of the validated SF-36) questionnaire, complemented by four additional questions gauging patient satisfaction.Co-primary outcomes The primary outcomes were the scores in four domains of the SF-36 questionnaire.Results 33 patients participated in the study. Univariate analysis revealed substantial improvement in three of the four SF-36 domains. Specifically, participants reported improvements in the mean SF-36 score (95% CI) from interviews 1 to 2 for ‘emotional role’ (24.2 (5.0–43.5)), ‘social functioning’ (22.0 (95%CI 10.8 to 33.2)) and ‘emotional well-being’ (11.9 (95%CI 5.6 to 18.2)). Furthermore, 97% of patients would recommend OPAT to others.Conclusion Patients experienced significant improvements in Health-Related Quality of Life (HRQoL) while enrolled in OPAT and the programme yields high patient satisfaction. Hospitals considering new OPAT programmes should include both patient satisfaction and HRQoL impact in their argument repertoire for the introduction of OPAT.